Exiles to the far Regions of the USSR in May–June, 1941 - Gurjanovas, Aleksandras (Genocidas ir rezistencija, 1997)
Between May and June 1941, mass deportations of large groups of the population were carried out from the territories occupied by the Soviet Union under the terms of the Soviet Union – Germany Pact of 23 August 1939 and subsequent treaties with Germany. This was the fourth wave of deportation to the mainland USSR since the outbreak of the Second World War. The first three were carried out in 1940 in the eastern territories of the pre–war Polish state. The 1941 deportation zone covered Estonia, Latvia, Lithuania, Bessarabia and Northern Bukovina, as well as western parts of Belarus and Ukraine. The following analysis will focus on the number of deportees based on archival material held in the archives of the Russian Federation.